From Islamic Populism to Patronage-Driven Populism: Prabowo's Evolving Electoral Strategy (2019–2024) - Syamsudin, Muhammad Hasan (State Islamic Institute of Kudus (IAIN Kudus), 2026)
This article aims to analyse the transformation of Prabowo Subianto's electoral strategy in the 2019 and 2024 Presidential Elections through the lens of the political economy of populism. The theoretical frameworks employed are Islamic populism (Hadiz, 2016), patronage-populism nexus (Kenny, 2017), and oligarchic populism (Aspinall, 2015). This study adopts a qualitative approach utilising a case study design, drawing upon data from reputable mass media outlets to academic literature. This article argues that the strategic shift executed by Prabowo was not merely rhetorical, but rather a profound transformation in the logic of voter mobilisation—shifting from a reliance on Islamic identity as a coalition cohesive to a patronage-driven populism rooted in the incumbent's patronage networks. Firstly, this is demonstrated by the shift in the actors within Prabowo's coalition away from the Islamist bloc in 2024. Secondly, it is evidenced by Prabowo's robust co-optation into Jokowi's patronage networks, which transformed Prabowo from an opposition figure into a pro-establishment actor. Thirdly, there is a discernible shift in Prabowo's electoral support base from puritanical Islamic strongholds to traditional PDI-P–Jokowi bastions. These findings revise Hadiz's thesis on the persistence of Islamic populism cohesion, extend Kenny's thesis that populist actors can emerge from the integration of dominant patronage networks, and update Aspinall's conceptualisation of oligarchic populism. This article proposes a new framework termed the Patronage-Driven Populism Shift to comprehend the nature of contemporary populism in Indonesia.